Correlation between exon 3 polymorphism of growth hormone receptor gene and the responses to rhGH therapy - Wei, Ying (Int J Clin Exp Pathol, 2015)
Objective: To investigate the correlation between the exon 3 polymorphism of growth hormone receptor (GHR) gene and the responses to the recombinant human growth hormone (rhGH) therapy in children with short stature. Methods: Forty-five growth hormone deficiency (GHD) children (male: 30, female: 15, aged 10.39±2.73 yrs) and twenty-five idiopathic short stature (ISS) children (male: 15, female: 10, aged 10.58±2.56 yrs) admitted to our hospital were included. The polymorphism of exon 3 of GHR gene was determined using multiple PCR amplification. Treatment duration for each subject was at least 12 months. On this basis, we evaluated the correlation between treatment efficiency of rhGH therapy and GHR exon 3 polymorphism, GHD, and treatment duration. Results: Significant difference was noted in the growth velocity (GV) of GHD children with a genotype of GHRfl compared with those with a genotype of GHRd3 (9.44±2.35 vs. 11.36±2.49, P < 0.05). Meanwhile, the GV of ISS patients with a genotype of GHRfl were remarkably decreased compared with those with a genotype of GHRd3 (8.74±2.36 vs. 11.18±2.44, P < 0.05). For the children with peak GH response of less than 5 ng/ml, statistical difference was noted in the GV of children with a genotype of GHRfl compared with those with a genotype of GHRd3 (9.55±2.76 vs. 10.84±1.53, P < 0.05). For the patients with peak GH response to clonidine or pyridostigmine bromide of > 5 ng/ml, a satisfactory response to rhGH therapy was noted in children with a genotype of GHRd3 compared with those of GHRfl (P < 0.05). Conclusions: GHRd3 was correlated with the response to rhGH therapy in children with short stature. For the patients with the same genotype, GHD caused no obvious effects on the final height. However, for the patients with peak GH response of > 5 ng/ml, a satisfactory response to rhGH therapy was noted in children with a genotype of GHRd3 compared with those of GHRfl (P < 0.05). A higher treatment efficiency was obtained in those received rhGH at an early age.